Biomass and carbon budgeting of land use types along elevation gradient in Central Himalayas. (20th February 2019) - Yadav, R.P.; Gupta, B.; Bhutia, P.L.; Bisht, J.K.; Pattanayak, A.
Abstract: Biomass of vegetation is a crucial variable for understanding the potential future changes of the climate system. In the present study dominant land use types i.e. agroforestry (AF), banjoak forest (BF), chirpine forest (CF), mixed forest (MF) and grasslands (GL) of Himalayan region was investigated for biomass production and carbon stock budgeting in vegetation as well as in soil. Among land use type's highest aboveground biomass was recorded in banjoak forest (BF), 0.69%, 9.42% and 40.16% more than chirpine forest (CF), mixed forest (MF) and agroforestry (AF). However it was more than 16 times higher than grasslands (GL). Herbage and/or crops aboveground biomass was 3.73%, 4.05%, 4.42% and 29.34% of the aboveground biomass of trees in BF, CF, MF and AF. Herbage aboveground biomass was 76.01% of total aboveground biomass in grasslands. Our results revealed that in AF crops biomass accounted for 19.41–26.60% and trees contributed 73.40–80.59% biomass in total biomass of land use. Likewise, similar contributions were recorded for belowground biomass and total biomass in land uses. Irrespective of land use types along elevation the total biomass including aboveground and belowground biomass significantly (P < 0.01) increased. Among land use types and along the elevation similar trend was recorded for vegetation carbon stock as it is the manifestation of biomass. Soil carbon density differed significantly in land use types with highest in BF and increased significantly along the elevation with highest at elevation E5 . Forest land uses stored 26.22% and 53.79% more total (vegetation + soil) carbon in than agroforestry and grasslands. The difference in carbon storage among land use types can be related to land use type, vegetation composition, their structural and functional characteristics viz., density, age and soil type. Thus, tree based land use types are more efficient for biomass production and carbon storage in changing climatic pattern. Highlights: Biomass production and carbon stock of vegetation significantly (P < 0.01) varied among land use types and along elevation. Among land use types highest soil carbon density was recorded in banjoak forest and significantly increased along elevation. Tree-based land uses stored more total carbon stock as compared to grasslands and it increased along increasing elevation. Biomass of vegetation is a crucial variable for understanding the potential future changes of the climate system.